METHODS OF DEVELOPING VOCAL-CHORAL SKILLS IN SINGING ACTIVITY (Web of Discoveries: Journal of Analysis and Inventions, 2025)
The article considers ways to improve vocal and choral skills in music lessons of secondary schools, the singing voice, singing culture, the formation of musical feelings in students, their spiritual world, deep philosophical and social thinking, as well as the valuable thoughts of the Eastern thinkers Al-Farabi, Ibn Sina, and the Greek philosopher Plato on the interrelation of musical education with moral education, the spiritual maturity of the individual, and the resolutions of the President of the Republic of Uzbekistan on the development of our national music.